Subacute Zinc Administration and L-NAME Caused an Increase of NO, Zinc, Lipoperoxidation, and Caspase-3 during a Cerebral Hypoxia-Ischemia Process in the Rat. (7th August 2013) - Blanco-Alvarez, Victor Manuel; Lopez-Moreno, Patricia; Soto-Rodriguez, Guadalupe; Martinez-Fong, Daniel; Rubio, Hector; Gonzalez-Barrios, Juan Antonio; Piña-Leyva, Celia; Torres-Soto, Maricela; Gomez-Villalobos, María de Jesus; Hernandez-Baltazar, Daniel; Brambila, Eduardo; Eguibar, José Ramon; et al.
Abstract : Zinc or L-NAME administration has been shown to be protector agents, decreasing oxidative stress and cell death. However, the treatment with zinc and L-NAME by intraperitoneal injection has not been studied. The aim of our work was to study the effect of zinc and L-NAME administration on nitrosative stress and cell death. Male Wistar rats were treated with ZnCl2 (2.5 mg/kg each 24 h, for 4 days) and N- ω -nitro-L-arginine-methyl ester (L-NAME, 10 mg/kg) on the day 5 (1 hour before a common carotid-artery occlusion (CCAO)). The temporoparietal cortex and hippocampus were dissected, and zinc, nitrites, and lipoperoxidation were assayed at different times. Cell death was assayed by histopathology using hematoxylin-eosin staining and caspase-3 active by immunostaining. The subacute administration of zinc before CCAO decreases the levels of zinc, nitrites, lipoperoxidation, and cell death in the late phase of the ischemia. L-NAME administration in the rats treated with zinc showed an increase of zinc levels in the early phase and increase of zinc, nitrites, and lipoperoxidation levels, cell death by necrosis, and the apoptosis in the late phase. These results suggest that the use of these two therapeutic strategies increased the injury caused by the CCAO, unlike the alone administration of zinc.